An Analysis of Lexical Relations in the Song ‘Someone You Loved’ by Lewis Capaldi from a Lexical Semantics Perspective - Junita Siska Nauli Saragih; Bernieke Anggita Ristia Damanik (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This research intends to examine the lexical connections present in the song “Someone You Loved” by Lewis Capaldi through the lens of lexical semantics. The study is centered on uncovering various categories of lexical relations, including synonymy, antonymy, hyponymy, and repetition found in the lyrics of the song. Utilizing a qualitative descriptive approach, the research gathers data from the song's lyrics and interprets it according to lexical semantics theories. The results indicate the presence of multiple lexical relations that enhance the emotional richness and significance of the lyrics. Synonymy serves to reinforce comparable concepts, while antonymy emphasizes differences in emotions, especially regarding love, grief, and isolation. Additionally, repetition is often observed, highlighting the emotional strength of the narrator’s experiences. These lexical connections not only improve the song’s artistic appeal but also assist listeners in grasping the deeper message. In summary, the incorporation of lexical relations within the song is crucial for transmitting meaning and emotional expression, making it a valuable topic for analysis in lexical semantics.